Familial risks for chronic obstructive pulmonary disease among siblings based on hospitalisations in Sweden. Issue 5 (15th April 2008) - Hemminki, K; Li, X; Sundquist, K; Sundquist, J
Abstract : Background: Chronic obstructive pulmonary disease (COPD) is a progressive disabling condition, for which tobacco smoking, environmental pollution, inherited α-antitrypsin deficiency and their interactions are predisposing factors. We carried out a family study on COPD in order to address the role of heritable and environmental risk factors at a population level. Methods: In a nationwide study on familial risks for COPD the Multigeneration Register on 0–72-year-old subjects was linked to the Hospital Discharge Register from years 1987 to 2004. Standardised incidence ratios (SIRs) were calculated for affected singleton siblings, twins and spouses by comparing them with those whose siblings or spouses had no hospitalisation for COPD. Results: More than 14 300 hospitalised cases and 604 affected siblings were identified. The familial SIR for obstructive chronic bronchitis was 4.65, which was higher for those diagnosed at young age but independent of sex or the age differences between the siblings. When both siblings were diagnosed with obstructive chronic bronchitis or emphysema the SIRs were 4.45 and 14.22, respectively. The SIR for obstructive chronic bronchitis in 24 twin pairs was 11.87. The SIR for spouses was about 1.6. Conclusions: The much higher risk for siblings of patients with COPD than the risk for spouses suggests that heritable effects underlie familial susceptibility to this disease. For the rare familial emphysema, α-antitrypsin deficiency may be an important cause. To what extent it also contributes to familial obstructive chronic bronchitis remains to be established. The anticipated gene-environment interactions with sufficient sample size need to be accommodated in future aetiological studies on COPD.